Chilean young learners' perspectives on their EFL lesson in primary schools - María-Jesus Inostroza A. (Universidad de Costa Rica, 2018)
Latest research in the field of applied linguists suggests that giving children a participatory and active role in the development of their foreign language skills could help teachers reveal overlooked aspects of language learning. Furthermore, challenging the role given to children in language learning research could provide useful insights about the learning processes. In this regard, little is known in the field of primary English language teaching in Latin America. In the case of Chile, the Curriculum Framework for primary English language teaching considers the relevance of children's experiences as part of their learning process; however, reference to their active involvement in this process is still scarce. This article aims at identifying the perspectives about the English lesson of a group of fourth graders from state-funded schools in Chile. Through an exploratory study of qualitative nature, the viewpoints of 16 children are collected through semi-structured group interviews. The data from the four group interviews are interpreted by content analysis resulting into two categories, and five subcategories related to likes, dislikes, perceived value of learning English, hands-on activities and feedback. The findings suggest that given the chance, children are able to consistently reflect on their learning process and experiences. These learners pointed out preferences for hands-on activities and the relevance of opportunities for obtaining feedback as contributing experiences for successful language learning. Similarly, these results illustrate that, by considering perspectives from outside applied linguistics, researchers could uncover factors present in the language learning process.